Anthocyanin suppresses the toxicity of Aβ deposits through diversion of molecular forms in in vitro and in vivo models of Alzheimer's disease. (January 2016) - Yamakawa, Miho Yoshida; Uchino, Kazuyuki; Watanabe, Yasuhiro; Adachi, Tadashi; Nakanishi, Mami; Ichino, Hikari; Hongo, Kunihiro; Mizobata, Tomohiro; Kobayashi, Saori; Nakashima, Kenji; Kawata, Yasushi
Abstract : Objectives: The pathogenesis of Alzheimer's disease (AD) is strongly correlated with the aggregation and deposition of the amyloid beta (Aβ1–42) peptide in fibrillar form, and many studies have shown that plant-derived polyphenols are capable of attenuating AD progression in various disease models. In this study, we set out to correlate the effects of anthocyanoside extracts ( Vaccinium myrtillus anthocyanoside (VMA)) obtained from bilberry on the in vitro progression of Aβ fibril formation with the in vivo effects of this compound on AD pathogenesis. Methods: Thioflavin T fluorescence assays and atomic force microscopy were used to monitor Aβ amyloid formation in in vitro assays. Effects of Aβ amyloids on cellular viability were assayed using cultured Neuro2a cells. Cognitive effects were probed using mice that simultaneously expressed mutant human Aβ precursor and mutant presenilin-2. Results: Addition of VMA inhibited the in vitro formation of Aβ peptide fibrils and also reduced the toxicity of these aggregates toward Neuro2a cells. A diet containing 1% VMA prevented the cognitive degeneration in AD mice. Curiously, this diet-derived retention of cognitive ability was not accompanied by a reduction in aggregate deposition in brains; rather, an increase in insoluble deposits was observed compared with mice raised on a control diet. Discussion: The paradoxical increase in insoluble deposits caused by VMA suggests that these polyphenols divert Aβ aggregation to an alternate, non-toxic form. This finding underscores the complex effects that polyphenol compounds may exert on amyloid deposition in vivo .